Physiological Properties of Tomato Varieties and Hybrids in Sheltered Structures - kizi, Kulmukhamedova Bakhtigul Anvarjon; Lapasovich, Sanakulov Akmal (American Journal of Biology and Natural Sciences, 2024)
Tomatoes (Solanum lycopersicum) are among the most economically important crops cultivated globally, particularly in sheltered structures such as greenhouses. These environments enable precise control over growing conditions, optimizing physiological traits like photosynthesis, nutrient absorption, and stress tolerance. This article explores the physiological properties of different tomato varieties and hybrids, focusing on growth, yield, and adaptation under controlled environments.